Long-term continuous partial nitritation-anammox reactor aeration optimization at different nitrogen loading rates for the treatment of ammonium rich digestate lagoon supernatant. (December 2020) - Yang, Sen; Xu, Shengnan; Boiocchi, Riccardo; Mohammed, Abdul; Li, Xinru; Ashbolt, Nicholas J.; Liu, Yang
Graphical abstract: Highlights: The effect of DO on nitritation-anammox was investigated in IFAS under different HRTs. The overall nitrogen removal rate was significantly increased with elevated DO concentrations. Anammox activity inhibition was observed at DO of 0.28−0.35 mg/L in the bulk liquid at HRT of 1.2 day. This study confirms the use of intermitted aeration as a strategy to effectively avoid NOB growth. Abstract: Dissolved oxygen (DO) is an important parameter for partial nitritation-anammox process but previously not evaluated for the treatment of digested biosolid thickening lagoon supernatant. Using intermittent aeration we investigated nitrogen removal from such supernatant in an integrated fixed film activated sludge (IFAS) process operated under a variety of hydraulic retention times (1.2–2.5 days). The overall nitrogen removal rate (NRR) was significantly increased (P < 0.01) from 0.26 ± 0.01 kg N m −3 d -1 at HRT of 2.5 days to 0.50 ± 0.01 kg N m -3 d -1 at HRT of 1.2 day. Higher nitrogen loading rates needed higher DO concentrations in order to cope with the increased oxygen demand by ammonium-oxidizing bacteria (AOB). Enhancing the DO concentration from 0.18 mg L -1 to 0.35 mg L -1 improved AOB activity. However, when the bulk liquid DO was in the range of 0.28−0.35 mg L -1, anammox activity inhibition was observed associated with a significant free nitrous acid (FNA) accumulation (21.70 ± 4.10 μg L -1 ). Batch studies confirmed the inhibition of anammox activity under high DO conditions (0.28−0.35 mg L -1 ). Aeration strategies, other than increasing the DO set points, should be investigated in order to be able to work at high nitrogen loading rates without compromising anammox activity.